Study of Chemical Multirepresentation on Chemical Bonding Material in Independent Curriculum Chemistry Textbooks - Fadila, Iffa; Aini, Faizah Qurrata (Journal of Educational Sciences, 2025)
Textbooks are one of the teaching materials that have an important role in understanding student representation. A meaningful approach can provide understanding to students by using images or visuals to illustrate different levels of representation in chemical phenomena contained in textbooks. One of the chemical materials that requires the role of chemical representation to provide a more realistic visualization for students about abstract chemical concepts is chemical bonding material. The concept in chemical phenomena that emphasizes three levels of chemical representation can provide a complete understanding if it is able to link the three levels of representation. The representations presented in the textbooks that were analyzed generally came from websites that were not scientifically trusted. This study aims to analyze the multi-representation of independent curriculum chemistry textbooks on chemical bonding material using five criteria developed by Gkitzia et al. (2011). The data sources in this study were six chemistry textbooks for the Independent Curriculum for SMA/MA which were compared with standard books. The results of this study indicate that the six textbooks generally have the following types of representation: (C1) multiple typology, but no mixed representation, (C2) explicit typology, (C3) fully related and related typology, (C4) typology of the existence of appropriate information, and (C5) fairly related typology.